The Political History of Sugar Law in Indonesia from Colonial to Contemporary Times - Widya Ari Dewi (PT. Global Research Collaboration, 2025)
Background: Sugar has historically functioned as a strategic commodity within Indonesia’s legal and political economy since the colonial period. Its governance has been structured through successive regulatory regimes that reflect shifting political authority, from Dutch colonial plantation law to post-independence state control and contemporary market stabilization policies. Despite major institutional transformations, core regulatory logics in land use, production management, and trade governance continue to demonstrate significant historical continuity. Objective: This study analyzes the historical development of sugar law in Indonesia from the colonial period to the contemporary era and examines how long-term legal continuity shapes current governance structures and persistent structural inequalities in the sugar industry. Method: This research employs a qualitative methodology using a historical legal approach combined with socio-legal interpretation. Data were collected through systematic library research of primary legal instruments, including colonial agrarian and plantation regulations, post-independence nationalization laws, and contemporary trade and import policies, supported by secondary academic literature. The data were analyzed using descriptive-analytical and comparative historical techniques to identify patterns of legal continuity and transformation across different historical periods. Findings: The findings indicate strong institutional continuity in sugar governance across colonial, post-independence, and contemporary periods. During the colonial era, legal instruments such as the Agrarische Wet 1870 and Suikerreglement established a production-oriented system based on land control, labor organization, and export regulation. In the post-independence period, Law No. 86 of 1958 on nationalization transferred ownership of sugar industries to the state but maintained centralized production logic. In the contemporary period, sugar governance is dominated by trade regulation and import policies under Presidential Regulation No. 71 of 2015, which function as short-term stabilization tools. However, these mechanisms have not resolved structural inequality, particularly the weak bargaining position of sugarcane farmers within the value chain. Conclusion: Sugar law in Indonesia has historically functioned as a regulatory system oriented toward production control and market stabilization rather than distributive justice. The persistence of colonial legal rationalities within modern governance structures indicates that structural reform is necessary to achieve more equitable and sustainable sugar sector governance. Scientific Contribution: This study develops a continuity-based legal framework for analyzing commodity governance by demonstrating that sugar regulation in Indonesia operates as a historically layered legal system shaped by path-dependent institutional structures. It contributes to socio-legal and legal-historical scholarship by showing that contemporary sugar policy cannot be fully understood without recognizing the persistence of colonial legal foundations within modern regulatory regimes.